Production and characterization of xylanase produced by submerged fermentation of Bacillus spp using pepper agricultural waste - Nair Mahenthran, Asha Asvinee (Universiti Malaysia Sarawak, UNIMAS, 2011)
A xylanase producer, Bacillus spp has been successfully isolated from pepper agricultural waste and characterized morphologically based on gram staining method. Then, the Bacillus spp was grown on xylan containing material which is corn cob to detect the presence of xylanase by determining the diameter of halos produced after stained with Congo red solution. Submerged fermentation was carried out to study the effects of various parameters such as incubation period, shaking speed, substrate concentration and inoculum concentration on xylanase production by Bacillus spp where pepper residues was used as the sole carbon source. The highest xylanase activity was recorded after 10 days of incubation time which was 36.67 U/mL. The xylanase produced by Bacillus spp showed the optimal activity under acidic condition at pH 5 and recorded as 124.99 U/mL and showed the optimal activity at temperature of 55 degree Celsius where the activity was recorded as 149.17 U/mL. The xylanase was observed to have the highest enzyme-substrate reaction after 15 minutes of incubation period which was recorded as 56.62 U/mL. Moreover, after an hour of incubation in acidic and alkaline pH, the enzyme retained 90% of its relative activity under acidic condition and retained 82% of its original activity at temperature 50 degrees Celsius after two hours of incubation.